ANALISIS PENGARUH CITRA MEREK, PERSEPSI KUALITAS, DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN PEMBELIAN MELALUI PERSEPSI NILAI SEBAGAI INTERVENING - Ramadhan Kurniawan, Agvi; Idris, Idris (Diponegoro Journal of Management, 2015)
High population growth and the high mobility of the people and coupled with high car ownership aspirations cause increased competition in the automotive industry. Automotive industry competition increased, causing the Honda Freed products less competitive with other products in the class MPV cars. This study aimed to examine the effect of brand image variables, perceived quality, and perceived risk on purchasing decisions Honda Freed in Semarang through the perception of value as intervening.            The total sample of 100 respondent owners and users of the Honda Freed is taken with a convenience / accidental sampling technique. Method of data analysts using path analysis method, the analysis includes: validity, reliability, classic assumption test, linear regression test, t test, F test, and Sobel test coefficient of determination.            The results of path analysis showed that the two independent variables, namely the brand image (0,382) and perceived quality (0,267) had a positive and significant relationship to the intervening variable that is the perception of value. There is one independent variable that has a negative relationship to the intervening variable is the perception of risk (-0,352). Intervening variables such as perceived value has a positive correlation (0,475) and parallel to the dependent variable